Evaluation and assessment of the survival of tooth implant supported prosthesis in tooth and implant supported rehabilitation cases with metal frameworks - Joshua Narde; Nabeel Ahmed; Maria Maddalena Marrapodi; Yuliia Siurkel; Vincenzo Ronsivalle; Marco Cicciù; Giuseppe Minervini (BMC, 2024)
Abstract Introduction Over the years, implant therapy has been a commonly used treatment option for individuals who are partially or totally edentulous, with a long-term success rate of over 90%. With significant advancements in biomaterials and technology, implant dentistry can now conduct prosthetic rehabilitations in the majority of patients catering to all types of needs. However, in order to meet the demands of a patient base that is always growing, new trends in implantology are emerging in recent years that are focused on minimally invasive surgery and financial sustainability. In certain clinical scenarios, connecting teeth and implants to support fixed partial prosthesis (FPPs) may be a predictable and workable course of treatment. Materials and methods 22 patients were selected for this study who had tooth and implant supported prosthesis placed as a final restoration. Out of these 22 patients; 12 were male and 10 were female patients. Implants were placed following proper protocol and if grafting procedures were required they were carried out. A second stage surgical procedure was carried out and delayed loading protocols were followed. The statistical analysis was done using the IBM SPSS 24.0, Chicago, USA. The survival of the implants and teeth were measured by the Kaplan Meier survival scale. Bone loss was assessed at baseline(upon loading), 12 months and 24 months. Results The implant survival rate was measured at 6 months, 12 months, 18 months and 24 months. At 24 months, one implant showed failure, so the survival rate of the implants were 95.4%. Bone loss of 1 mm was seen around one implant at 12 months. Bone loss of 1 and 2 mm was present around two implants and one implant respectively at 24 months. Conclusion From the results of this study, we can conclude that tooth implant supported prosthesis show very good survival when used in rehabilitation cases.